Quasi Emulsion Solvent Diffusion Modification of Underutilized Chenopodium album Starch and its Characterization - Singh, Renuka; Singh, Sukhcharn; Saxena, D.C. (Asian Journal of Chemistry, 2022)
The present study was designed to investigate the changes occur on Chenopodium album starch (CAS) after modification through quasi emulsion solvent diffusion (QESD) method. Modification of starch was carried out by HCl (0.1, 0.25, 0.50, 0.75 and 1M) followed by precipitation. The QESD modification significantly reduced the amylose content, water absorption capacity, oil absorption capacity, solubility as well as swelling power of treated starch. Gelatinization behaviour of modified starch showed an increase in pasting temperature. The SEM images showed the formation of regular and spherical shaped larger starch particles. There was an improvement in crystallinity from 20.01 to 29.86% after modification as shown in X-ray analysis. Overall, it indicates that QESD treatment results into formation of spherical crystalline agglomerates.